Iron reduction process and antimony behavior change in paddy soils under stationary flooding conditions. (July 2022) - Long, Jiumei; Zhou, Dongsheng; Huang, Yayuan; Yi, Zhengji; Bin, Dongmei; Luo, Yuanlai; Wang, Jing; Deng, Jingheng; Lei, Ming
Abstract: Although iron reduction coupled with antimony (Sb) behavior change has attracted increasing interest in recent years, this process has not yet been well addressed in paddy soils under natural flooding conditions. This study investigates the iron reduction process in paddy soils using a stationary flooding incubation experiment. The paddy soils used in the study contained 199, 329 and 450 mg/kg of Sb (referred to as LS, MS and HS, respectively). Results showed that iron reduction lasted for 12–14 d under simulated flooding conditions at 25 °C, with the highest total Fe(II) being 778, 791 and 782 mg/kg in LS, MS and HS, respectively. Through the iron reduction process, easily reducible iron (Fe2) and reducible iron (Fe3) decreased by 26.1–38.4% and 4.03–12.8%, respectively, indicating that small fractions of iron oxides underwent reductive dissolution. The abundant phyla of iron-reducing bacteria in these soils were Proteobacteria, Firmicutes and Actinobacteriota. Moreover, up to 14 genera were identified as abundant iron-reducing bacteria in these paddy soils. Among, the most abundant genera were Azospirillum and Magnetospirillum, which are also known to mediate the iron nutrition supply for plants and magnetite formation, respectively. Along with iron reduction, iron oxide-incorporated Sb decreased by 7.87–17.3%, while soil surface-bound Sb increased by 42.4–60.4%. This demonstrates that substantial Sb released from iron reductive dissolution was adsorbed on the soil surface. In addition, the total aqueous Sb increased by 24.9–33.0 μg/L through iron reduction in these flooding soils, indicating that iron reduction promoted Sb mobilization in paddy soils under flooding conditions. Sb was synchronously reduced to Sb(III), with Sb(III) accounting for 51.1–59.4% of the total citric acid extracted Sb at the end of iron reduction. However, the aqueous Sb(III) was lower by orders of magnitude than the corresponding Sb(V) in these soils. This might imply that the strong adsorption affinity of Sb(III) to the soil solid facilitated the increase in soil surface-bound Sb in all flooded paddy soils. Highlights: Only small parts of iron oxides underwent reductive dissolution. The most abundant IRB genera might also be efficient in iron nutrition supply and magnetite formation. Iron reduction released Sb to porewater and soil surface. Sb reduction coincided with iron reduction. Although more than half of Sb was reduced, Sb(III) in porewater remained low.